Analysis of numeration literacy ability in solving hots questions on two-dimensional figure material fifth-grade students - Kusumadewi, Rida Fironika; Lutog, Marevic Jean P.; Aretosa, Cinta Jenitra Jihan; Hastomo, Hastomo (Jurnal Ilmiah Pendidikan Dasar, 2024)
Students' low numeracy literacy skills in connecting mathematics with real-life applications and solving HOTS questions effectively. This research aims to find out how the numeracy literacy skills of class V students are in flat plane material. This research uses a qualitative case study type method with the Miles and Huberman model.    The research results show that the numeracy literacy skills of class V students at SDI Sultan Agung 1.3 Semarang are still quite low. Of the 22 students, 14 students had low numeracy abilities, 5 students had medium numeracy abilities, and 3 students had high numeracy abilities These findings also show that the majority of students have difficulty with word problems that require in-depth understanding of the context, indicating a lack of students' skills in working on HOTS-based questions and a lack of exposure to numeracy literacy activities. The findings of this research can be a basis for teachers to develop more effective learning strategies in improving students' numeracy literacy skills. This research provides a new view on how numeracy literacy can influence students' abilities in solving HOTS questions, especially on the topic of plane figures.